"Shaping heritage identity in visual arts and interior design" (Comprehensive Journal of Science, 2025)
This research examines the formulation of heritage identity in visual arts and interior design as a topic related to the study of cultural heritage presence in contemporary artistic and design practices. The study is based on the importance of heritage identity as a reflection of the cultural specificity of societies, represented through visual and symbolic elements expressed in artistic works and interior spaces.The research aims to describe the manifestation of heritage identity in visual arts and interior design by tracing the forms of employing heritage elements such as ornaments, symbols, materials, and colors derived from the local environment, and how they appear in contemporary artistic and design production, without interpretation or analysis, but through a descriptive presentation of the phenomenon.The study adopts the descriptive approach, which focuses on describing phenomena as they exist in reality, based on relevant literature and previous studies. It shows that heritage identity appears in visual arts through visual compositions inspired by heritage, and in interior design through the integration of traditional elements within spaces reflecting cultural identity.The study concludes that heritage identity is a visible element in both visual arts and interior design, expressed through various forms of utilization that enhance cultural identity within contemporary contexts.
Keywords: Heritage identity, visual arts, interior design, cultural heritage, visual expression, traditional ornaments, contemporary design.